Case report: A novel ACTA1 variant in a patient with nemaline rods and increased glycogen deposition - Piga, Daniela; Rimoldi, Martina; Magri, Francesca; Zanotti, Simona; Napoli, Laura; Ripolone, Michela; Pagliarani, Serena; Ciscato, Patrizia; Velardo, Daniele; D’Amico, Adele; Bertini, Enrico; Comi, Giacomo Pietro; et al. (Frontiers in Neurology, 2024)
Background Congenital myopathies are a group of heterogeneous inherited disorders, mainly characterized by early-onset hypotonia and muscle weakness. The spectrum of clinical phenotype can be highly variable, going from very mild to severe presentations. The course also varies broadly resulting in a fatal outcome in the most severe cases but can either be benign or lead to an amelioration even in severe presentations. Muscle biopsy analysis is crucial for the identification of pathognomonic morphological features, such as core areas, nemaline bodies or rods, nuclear centralizations and congenital type 1 fibers disproportion. However, multiple abnormalities in the same muscle can be observed, making more complex the myopathological scenario. Case presentation Here, we describe an Italian newborn presenting with severe hypotonia, respiratory insufficiency, inability to suck and swallow, requiring mechanical ventilation and gastrostomy feeding. Muscle biopsy analyzed by light microscopy showed the presence of vacuoles filled with glycogen, suggesting a metabolic myopathy, but also fuchsinophilic inclusions. Ultrastructural studies confirmed the presence of normally structured glycogen, and the presence of minirods, directing the diagnostic hypothesis toward a nemaline myopathy. An expanded Next Generation Sequencing analysis targeting congenital myopathies genes revealed the presence of a novel heterozygous c.965 T > A p. (Leu322Gln) variant in the ACTA1 gene, which encodes the skeletal muscle alpha-actin. Conclusion Our case expands the repertoire of molecular and pathological features observed in actinopathies. We highlight the value of ultrastructural examination to investigate the abnormalities detected at the histological level. We also emphasized the use of expanded gene panels in the molecular analysis of neuromuscular patients, especially for those ones presenting multiple bioptic alterations.